Environment and development : basic principles, human activities, and environmental implications - Poulopoulos, Stavros G.; Inglezakis, Vassilis J. (Elsevier, 2016)
This book focuses on the adverse impacts of human activities and development on both natural and inhabited environments. It covers associated problems and solutions for achieving harmonic sustainable development in a range of environments and presents the latest research findings in global environmental policy.